Kompetensi Perawat dalam Perawatan Spiritual di Ruang Rawat Inap RSUD Labuang Baji Makassar - Nini Niatullah Aliyati; Mujiburrahman Mujiburrahman (Jurnal Rumpun Ilmu Kesehatan, 2025)
The purpose of this study was to determine the care skills of nurses. In carrying out their profession, care is required to improve skills which is a process that leads to professionalism. The process begins with the perception of nurses in seeing conditions and solving problems, one of which is carrying out the application of nursing care to clients. The application of nursing care provided by nurses cannot be separated from spiritual aspects which are an integral part of the nurse's interaction with clients. Nurses together with special spiritual officers in the hospital try to help meet the spiritual needs of clients as part of the client's overall needs, among others by facilitating the fulfillment of these client needs, even though nurses and clients do not have the same beliefs and religions. In the application of spiritual nursing care is influenced by several factors, namely intellectual skills where the nurse's intellect will be very influential in the application of care. With data collection methods, namely observation, documentation and questionnaires. The population and sample are Samples In this study, the sampling technique used was purposive sampling, namely the sample taken was 50 nurses who served in four rooms of the Inpatient Hospital Labuang Baji Makassar.